Increasing civil participation in public control at the municipal level - T. N. Mikheeva; D. S. Mikheev (Правоприменение)
The subject of the research is public control, which is considered to be a modern instrument of citizens' participation in the cases of local self-government. It significantly complements the basic mechanisms of direct democracy at the municipal level, providing the population with the opportunity to evaluate the activities of local authorities.The purpose of the study is to consider public control from the perspective of its implementation at the municipal level. The key task is to find and justify additional subjects close to this level, revealing new opportunities for a more active response of residents to the short-comings of the local authorities. The most important in this series is the definition of citizens’ role and the public structures they create in the implementation of public control. Another significant task is to develop recommendations for improving the legal regulation of public control at the municipal level.The methodology. The solution of the set tasks is supposed to be carried out using a number of cognition methods with the analysis as the leading one. It has become determinant in the study of scientific sources and the empirical base. The doctrinal method was used to study the opinions of legal scholars on the issue under discussion. Working with legislation regulating public control was based on a formal and logical method. To formulate the research conclusions the authors used general scientific methods of synthesis and analogy, as well as general-to-specific method.The main results. The analysis showed that the public chambers (councils) of municipalities created by local governments to exercise public control are to a certain extent dependent on these bodies. We focused on more independent segments of the local community that are not included in the law, but show examples of social activity. The resource of society increases many times if three new subjects at the municipal level are given legislative access to public control: citizens, local public associations, and organized groups of citizens – territorial public self-governments that successfully operate in the local territories of municipalities. Conclusions. The recommendations presented in the study are the basis for improving domestic legislation on public control and local self-government. Filling in the legislative gaps should have a positive impact on law enforcement practice. The practical nature of the received conclusions and proposals is that they open up new opportunities for the representatives of the local community: (a) to protect their rights and legitimate interests with the help of the tools of public control; (b) to promptly correct mistakes and miscalculations of local authorities. The authors are convinced that the development of democracy on the scale of such a huge state as the Russian Federation should start with a small entity — its entrance hall, street, neighborhood, settlement, and city.